Synthesis of the Sex Pheromone of the Tea Tussock Moth Based on a Resource Chemistry Strategy - Hong-Li Zhang (Molecules, 2018)
Synthesis of the sex pheromone of the tea tussock moth in 33% overall yield over 10 steps was achieved. Moreover, the chiral pool concept was applied in the asymmetric synthesis. The synthesis used a chemical available on a large-scale from recycling of wastewater from the steroid industry. The carbon skeleton was constructed using the C4+C5+C8 strategy. Based on this strategy, the original chiral center was totally retained.